Poultry feeding: fifty years of research at the Institute of Animal Science - Hidalgo, Katia; Rodríguez, Bárbara (Cuban Journal of Agricultural Science, 2016)
This paper is aimed at reviewing the information obtained from studies carried out at the Institute of Animal Science related to poultry feeding in the period 1965-2014. Aspects concerning the utilization of products and by-products of sugar cane, by-products of the sugar industry, cassava products and by-products, energetic and protein sources, minerals as well as additives are considered. Advances attained in import substitutions are reported.Key words: poultry, feeding, agroindustrial products and by-products